How many conidia are required for wound infection of apple plants by Neonectria ditissima - Walter, M.; Roy, S.; Fisher, B.M.; Mackle, L.; Amponsah, N.T.; Curnow, T.; Campbell, R.E.; Braun, P.; Reineke, A.; Scheper, R.W.A. (New Zealand Plant Protection, 2016)
A series of experiments using potted plants in a glasshouse detached laterals in the laboratory and trees in the fi eld were undertaken to study wound size and number of Neonectria ditissima conidia required to produce European canker infections on freshlymade branch wounds in the apple cultivars Royal Gala and Scilate Th e wound types were needle and pin injuries rasp wounds and pruning cuts Spore concentrations from 102 to 106 conidia/ml and two inoculation methods (droplet and mist) were used Disease expression varied for the different assay types probably due to the conduciveness for infection of the diff erent incubation conditions Overall there was little eff ect on pathogen colonisation and lesion development based on injury type inoculation method or spore concentration >103 conidia/ml For freshlymade wounds such as pruning cuts or rasp wounds only three conidia were required for infection initiation in the glasshouse under highly conducive conditions 12 conidia in the laboratory on detached shoots and 10 to 30 conidia in the fi eld